Seasonal effects in a lake sediment archaeal community of the brazilian savanna - Rodrigues, Thiago (2014)
The Cerrado is a biome that corresponds to 24% of Brazil’s territory. Only recently microbial communities of this biome have been investigated. Here we describe for the first time the diversity of archaeal communities from freshwater lake sediments of the Cerrado in the dry season and in the transition period between the dry and rainy seasons, when the first rains occur. Gene libraries were constructed, using Archaea-specific primers for the 16S rRNA and amoA genes. Analysis revealed marked differences between the archaeal communities found in the two seasons. I.1a and I.1c Thaumarchaeota were found in greater numbers in the transition period, while MCG Archaea was dominant on the dry season. Methanogens were only found in the dry season. Analysis of 16S rRNA sequences revealed lower diversity on the transition period. We detected archaeal amoA sequences in both seasons, but there were more OTUs during the dry season. These sequences were within the same cluster as Nitrosotalea devanaterra’s amoA gene. The principal coordinate analysis (PCoA) test revealed significant differences between samples from different seasons. These results provide information on archaeal diversity in freshwater lake sediments of the Cerrado and indicates that rain is likely a factor that impacts these communities.